Cancer Stem Cells in Head and Neck Metastatic Malignant Melanoma Express Components of the Renin-Angiotensin System - Sam Siljee; Tessa Pilkington; Helen D. Brasch; Nicholas Bockett; Josie Patel; Erin Paterson; Paul F. Davis; Swee T. Tan (Life, 2020)
Components of the renin-angiotensin system (RAS) are expressed by cancer stem cells (CSCs) in many cancer types. We here investigated expression of the RAS by the CSC subpopulations in human head and neck metastatic malignant melanoma (HNmMM) tissue samples and HNmMM-derived primary cell lines. Immunohistochemical staining demonstrated expression of pro-renin receptor (PRR), angiotensin-converting enzyme (ACE), and angiotensin II receptor 2 (AT2R) in all; renin in one; and ACE2 in none of the 20 HNmMM tissue samples. PRR was localized to cells within the tumor nests (TNs), while AT2R was expressed by cells within the TNs and the peritumoral stroma (PTS). ACE was localized to the endothelium of the tumor microvessels within the PTS. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) detected transcripts for PRR, ACE, ACE2, and AT1R, in all the five HNmMM tissue samples and four HNmMM-derived primary cell lines; renin in one tissue sample and one cell line, and AT2R in none of the five HNmMM tissue samples and cell lines. Western blotting showed variable expression of ACE, PRR, and AT2R, but not ACE2, in six HNmMM tissue samples and two HNmMM-derived primary cell lines. Immunofluorescence staining of two HNmMM tissue samples demonstrated expression of PRR and AT2R by the SOX2+ CSCs within the TNs and the OCT4+ CSCs within the PTS, with ACE localized to the endothelium of the tumor microvessels within the PTS.